Complete Genome Sequence of Phascolarctobacterium faecium JCM 30894, a Succinate-Utilizing Bacterium Isolated from Human Feces - Ogata, Yusuke (Microbiol Resour Announc, 2019)
Phascolarctobacterium faecium is an anaerobic microbe known as a member of the human gut microbiome. Here, we report the complete genome sequence of Phascolarctobacterium faecium JCM 30894 and the elucidation of the mechanism for utilization of succinate by this bacterium based on the genome analysis.